Pendidikan Agama Di Era Digital: Menjaga Spiritualitas Di Tengah Derasnya Arus Informasi - Nur wahyuni, Lathyva; Indira Ainia, Malika; Halifa Ramadhani, Moh. (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The digital transformation that has hit various aspects of life has also influenced religious education patterns, especially in efforts to maintain spiritual values ​​amidst the rapid flow of information. One of the relevant figures in this context is Ustadz Hanan Attaki who was able to utilize digital platforms effectively to foster the spirituality of the younger generation. This research aims to analyze the digital da'wah strategy carried out by Ustadz Hanan Attaki and its impact in strengthening religious and spiritual values ​​among generation z. The method used is literature study, by reviewing various previous literature and previous research related to digital da'wah and religious education. The results of the study show that Ustadz Hanan Attaki has succeeded in utilizing social media such as Instagram, YouTube and TikTok to convey religious messages with a creative, relevant and communicative approach. The relaxed but meaningful style of preaching, the use of language familiar to young people, and the integration of contemporary issues such as mental health, have proven effective in increasing religious awareness, strengthening spiritual values, and encouraging active involvement in religious activities